'My Usual Despicable Hold on Life': The View from Sylvia Townsend Warner's Diaries (The Sylvia Townsend Warner Society Lecture 2021). Issue 2 (21st June 2022) - Trotter, David
Abstract : page_97 other This lecture draws on published and unpublished material from the 38 notebooks of different sizes, shapes and states of repair archived in the Dorset History Centre to argue that the richly informative diary Sylvia Townsend Warner began to keep in 1927 provides a vital resource for a fuller understanding of the fiction as well as of the life. In particular I aim to demonstrate that melancholy constitutes a defining preoccupation in both. I establish contexts for this preoccupation in Warner's erudition and in the work of Theodore and Llewellyn Powys, while also proposing some instructive broader parallels with the contemporary writings of Walter Benjamin. Both, for example, took a strong interest in the radical Bohemian culture which flourished in Paris before and during the 1848 revolutions: Summer Will Show (1936), set in that place at that time, is my main literary text. Other expressions of melancholy examined include diary entries concerning two of the cats in Warner's life and a hitherto unpublished poem provoked by the revival of Valentine Ackland's affair with Elizabeth Wade White in the summer of 1949.